Studi komparative faktor penentu kemiskinan provinsi di Sumatera dengan pertumbuhan ekonomi sebagai variabel intervening - Rahmadi, Selamet; Hastuti, Dwi; Parmadi, Parmadi; Parkhurst, Helen (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to identify the determining factors of poverty in the provinces of Sumatra and analyze the role of economic growth as an intervening variable in the relationship between these factors and the poverty level. The data used in this study are secondary data from various sources, including the Central Bureau of Statistics (BPS) and the Ministry of Finance. The analytical methods employed include descriptive analysis, regression analysis, and path analysis.The findings of the study reveal significant differences in the determining factors of poverty among the provinces in Sumatra. Significant factors in determining the poverty level include education level, access to healthcare services, unemployment rate, and urbanization rate. Additionally, economic growth has been proven to play a crucial role as an intervening variable in the relationship between these factors and the poverty level. High economic growth can reduce poverty rates by improving employment opportunities, income levels, and access to public services.This research provides a deeper understanding of the determining factors of poverty in the provinces of Sumatra and highlights the importance of economic growth in reducing poverty levels. These findings can serve as a basis for the government and other stakeholders in designing effective policies to alleviate poverty in Sumatra. Furthermore, this study can also serve as a reference for further research in this field.